Age and Prostate-Specific Antigen Level Prior to Diagnosis Predict Risk of Death from Prostate Cancer - MacKintosh, F. Roy; Sprenkle, Preston C.; Walter, Louise C.; Rawson, Lori; Karnes, R. Jeffrey; Morrell, Christopher H.; Kattan, Michael W.; Nawaf, Cayce B.; Neville, Thomas B. (Frontiers in Oncology, 2016)
A single early prostate specific antigen (PSA) level has been correlated with a higher likelihood of prostate cancer diagnosis and death in younger men. PSA testing in older men has been considered of limited utility. We evaluated prostate cancer death in relation to age and PSA level immediately prior to prostate cancer diagnosis. Using the Veterans Affairs database we identified 230,081 men aged 50-89 years diagnosed with prostate cancer and at least one prior PSA test between 1999 and 2009. Prostate cancer-specific death over time was calculated for patients stratified by age group (eg.50-59, through 80-89) and PSA range at diagnosis (10 ranges) using Kaplan-Meier methods. Risk of 10-year prostate cancer mortality across age and PSA was compared using log-Rank tests with a Bonferroni adjustment for multiple testing. 10.5% of men diagnosed with prostate cancer died of cancer during the 10-year study period (mean follow-up= 3.7 years). Higher PSA values prior to diagnosis predict a higher risk of death in all age groups (p<0.0001). Within the same PSA range older age groups are at increased risk for death from prostate cancer (p<0.0001). For PSA of 7-10 ng/mL, cancer-specific death 10 years after diagnosis increased from 7% for age 50-59 to 51% for age 80-89. Men older than 70 years are more likely to die of prostate cancer at any PSA level than younger men, suggesting prostate cancer remains a significant problem among older men (even those age 80+) and deserves additional study.